Comparative approaches to program planning - Netting, F. Ellen (John Wiley & Sons, 2008)
This book will demonstrate its value among students and practitioners alike. I imagine using it with undergraduates in community practice courses, in a graduate advanced practice seminar as well as with leaders in local nonprofits....This is the book I’ve been waiting for. It provides not only a linear approach to program design, but gives language to the tacit knowledge many planners have of the circular nature of their work. Both linear and circular thinking are important to planning processes and now we have a resource for teaching.